Actuarial Costing of Universal Health Insurance and Coverage in Indonesia : Options and Preliminary Results - Guerard, Yves; Wiener, Mitch; Rokx, Claudia; Schieber, George; Harimurti, Pandu; Pambudi, Eko; Tandon, Ajay (World Bank, Washington, DC, 2017)
This series is produced by the Health, Nutrition, and Population family (HNP) of the World Bank's Human Development Network (HDN). The papers in this series aim to provide a vehicle for publishing preliminary and unpolished results on HNP topics to encourage discussion and debate. The cost of a health insurance program will largely be determined by the size and composition of the covered population, the benefit package, cost sharing arrangements, the current and future supply of health care providers and facilities, and the provider payment mechanisms used. This note summarizes in broad strokes the subset of the possible Universal Coverage (UC) transition scenarios and their related costs in Indonesia. These scenarios were selected based on initial discussions with key stakeholders, and further broad-based discussion with stakeholders will be needed to finalize the design, financing and transition options. This note shows how decisions regarding the transition steps, benefit package and the choice of eligible population affect public Health Insurance (HI) expenditures as Indonesia transitions to UC. This work follows closely the earlier World Bank report health financing in Indonesia; a road map for reform.